(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Il concordato nelle dinamiche delle relazioni tra Chiesa cattolica e Stati islamici - 2. Concordato e libertà religiosa nei Paesi islamici - 3. Gli accordi bilaterali sottoscritti dalla Santa Sede in questi speciali “territori di missione” - 4. La tutela delle minoranze religiose nella Dichiarazione di Al-Azhar e la possibile apertura di nuove frontiere delle dinamiche concordatarie. The concordat dynamics between Holy See and Islamic State ABSTRACT: The article analyzes the concordat dynamics between Holy See and Islamic States developed after the Second Vatican Council. The concordat, in its various forms, is the main instrument through which is regulated the system of relations between States and Catholic Church. Its use has been tested successfully in various Islamic States, and sometimes even with heterogeneous formulas, because of differences that distinguish the individual systems, trying to translate the concepts of autonomous of Church and collaboration with States in forms legal acceptable to Muslim tradition countries. The exhortations in the Al-Azhar Declaration are directly connected with the possible development of bilateral activities between Holy See and other Islamic countries and this can also strengthen the peace among peoples and the interfaith dialogue.